The effects of sodium alendronate on socket healing after tooth extraction: a systematic review of animal studies - Nilo Guliberto Martins CHAVARRY; Pedro Villas Boas ABREU; Eduardo Jorge FERES-FILHO; Daniele Masterson Tavares PEREIRA; Lucianne Cople MAIA; Rafael Scaf De MOLON (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The aim of this systematic review was to answer the following question: "Does alendronate, a nitrogen-containing bisphosphonate, improve or impair alveolar socket healing after tooth extraction in animal models"? To this end, a systematic review of the literature was carried out in PubMed, Scopus, LILACS, Web of Science, as well as in the gray literature up to May 2023. Preclinical studies that evaluated alveolar healing after tooth extraction and the intake of sodium alendronate compared with placebo were included. Two investigators were responsible for screening the articles independently, extracting the data, and assessing their quality through the SYRCLE's RoB tool for randomized trials in animal studies. The study selection process, study characteristics, risk of bias in studies, impact of alendronate on bone healing, and certainty of evidence were described in text and table formats. Methodological differences among the studies were restricted to the synthesis methods. The synthesis of qualitative results followed the Synthesis Without Meta-analysis (SWiM) reporting guideline. From the 19 included studies, five were considered to have low risk, three were of unclear risk, and eleven presented a high risk of bias. The studies were considered heterogeneous regarding alendronate posology, including its dosage and route of administration. Furthermore, a variety of animal species, different age ranges, diverse teeth extracted, and exposure or not to ovariectomy contributed to the lack of parity of the selected studies. Our results indicated that alendronate monotherapy negatively affects the early phase of wound healing after tooth extraction in preclinical studies, suggesting that the bone resorption process after tooth extraction in animals treated with alendronate might impair the bone healing process of the extraction socket. In conclusion, alendronate administration restrains bone resorption, thereby delaying alveolar socket healing . Future studies should be conducted to validate these findings and to better understand the effects of alendronate therapy on oral tissues.